Perancangan Jembatan Koneksi Bangunan Pada Plaza Utama Al-Amin Living Lab Dan Industrial Park Di Desa Sampe Cita, Kecamatan Kutalimbaru - Wisdianti, Dara; Novalinda, Novalinda; Sigit, Faurantia Forlana; Siregar, Ida Khairani (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2024)
The design of a building connection bridge at the main plaza is a crucial step in urban infrastructure development, enabling pedestrians to move safely and efficiently between various key points within an area. This study aims to understand the design of the connection bridge at the main plaza of Al-Amin Living Lab and Industrial Park in Sampe Cita Village, Kutalimbaru District, and how it will serve pedestrians. The research subject is the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, with the observed parameters being the physical and non-physical conditions of the design location. The results of this study show that the facilities and infrastructure of the connection bridge for the Mixed-Use Building of Al-Amin Living Lab and Industrial Park consist of circulation pathways connecting the Mixed-Use buildings and a viewing deck, and the design direction of the Mixed-Use Building of Al-Amin Living Lab and Industrial Park meets the criteria.